2012
DOI: 10.2151/jmsj.2012-a05
|View full text |Cite
|
Sign up to set email alerts
|

Summertime Temperature Extremes over Japan in the Late 21st Century Projected by a High-Resolution Regional Climate Model

Abstract: Future changes in summertime temperature extremes over Japan are projected by a well-developed regional climate model (RCM) with a spatial resolution of 5 km. The performance of the RCM with respect to temperature in the present climate is evaluated first based on observations. Although the di¤erences in the biases (from observations) of daily temperatures between the RCM and the driving atmospheric general circulation model (AGCM) simulations are not statistically significant, root-mean-square errors (from ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Another uncertainty is that our runs are continuously warming, and it is possible that an equilibrium world at any given temperature may experience a different occurrence of extremes than in the runs in this paper. Additionally, since an increasing proportion of the population is expected to live in dense metropolitan areas, there is also the possibility that actual heat and humidity extremes that populations experience could be more severe than the gridded data due to local phenomena such as the urban heat island effect (Murata et al, 2012). Statistical or dynamical downscaling could be used for a more detailed analysis (Dibike and Coulibaly, 2006;Wood et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another uncertainty is that our runs are continuously warming, and it is possible that an equilibrium world at any given temperature may experience a different occurrence of extremes than in the runs in this paper. Additionally, since an increasing proportion of the population is expected to live in dense metropolitan areas, there is also the possibility that actual heat and humidity extremes that populations experience could be more severe than the gridded data due to local phenomena such as the urban heat island effect (Murata et al, 2012). Statistical or dynamical downscaling could be used for a more detailed analysis (Dibike and Coulibaly, 2006;Wood et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has attempted to distinguish the origin and mechanisms of unforced variability in temperature and temperature extremes (Meehl et al, 2007;Zhang et al, 2020;Birk et al, 2010). To probe the statistical modes of variability affecting this ensemble spread and to identify the under-lying physical mechanisms, an empirical orthogonal function (EOF) analysis (North, 1984) was performed on the detrended and normalized time series of deadly days and tropical nights for the 15 cities. For each city, the 28 ensemble members are concatenated together (total of 28 × 150 years) in order for all ensembles to share the same EOF.…”
Section: Impact Of Unforced Variability In Climate On Regional Heat Extremesmentioning
confidence: 99%
“…Downscaling with the 5-km mesh NHRCM is then performed by nesting within the results of the 20-km AGCM. Further downscaling with the 2-km mesh It is not our intention in this paper to review NHRCM and related results, as that will be found elsewhere (e.g., Wakazuki et al 2007;Nakamura et al 2008;Kanada et al 2008 Kanada et al , 2010a Kanada et al , 2010b Kanada et al , 2014Nakano et al 2010Nakano et al , 2011Nakano et al , 2012Murata et al 2012) and in this special issue. We rather limit ourselves to three projects recently conducted or being continuing, which uses the NHRCM embedded within the MRI high-resolution AGCM.…”
Section: Further Dynamical Downscaling By the Mri Regional Climate Momentioning
confidence: 91%
“…To the best of our knowledge, the future evolution of foehn winds has not been studied, even though they significantly affect ETEs in Japan, with the exception of Murata et al (2012), who showed that future atmospheric conditions should facilitate the intensification of foehn winds on Hokkaido Island, which is located north of the Japanese mainland. However, this case study was limited to Hokkaido Island, where ETEs are rare.…”
Section: Introductionmentioning
confidence: 99%